Pengaruh suplementasi kalsium butirat dalam ransum terhadap kecernaan nutrien, performa produksi dan kualitas telur ayam umur 75 minggu - Rizki Palupi; Fitri Nova Liya Lubis; Sofia Sandi; Angga Rian Arjuna; Chareldo Satori; Mutia Nurrahmadani (Livestock and Animal Research, 2022)
Objective: To determine the digestibility of laying hens ration supplemented with calcium butyrate, and its effect on the production and quality of the eggs produced.Methods: This study used a completely randomized design (CRD) with 4 treatments and each treatment consisted of 5 replicates. The treatment method was dietary calcium butyrate supplementation, specifically: R0 = Without calcium butyrate supplement (control), R1 = supplemented of 0.175 g/kg calcium butyrate on diet, R2 = supplemented of 0.350 g/kg calcium butyrate on diet, and R3 = supplemented of 0.525 g/kg calcium butyrate on diet. The observed parameters include the digestibility of substances in the feed; crude protein and crude fiber digestibility, production performance including ration consumption, egg production and feed conversion. Then measure egg quality including egg weight, egg white weight, egg yolk weight, Haugh unit value, weight eggshell and eggshell thickness.Results: The results showed that calcium butyrate supplementation in the ration of laying hens in the third production phase had no significant effect (P>0.05) on nutrient digestibility, egg production performance, but significantly (P<0.05) on eggshell quality.Conclusions: The conclusion of the study was that calcium butyrate supplementation up to 0.525 g/kg in the ration of laying hens had not been able to increase the digestibility of crude protein and digestibility of crude fiber in the ration, and had not been able to increase egg production and feed efficiency, but could improve the quality of the eggshell produced. Egg shell thickness increased by 21.21% compared to without the addition of calcium butyrate in the ration.